Progress in Social Psychiatry in Japan An Approach to Psychiatric Epidemiology - Nakane, Yoshibumi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2012)
Social psychiatry is a multidisciplinary field that analyzes mechanisms of mental health issues comprehensively to contribute to society using the findings. These findings include biological, psychological, and social aspects and are based on psychiatry and connected with a wide variety of academic fields, including psychology, sociology, law, economics, and religious studies. Epidemiological research in psychiatry is a field of study in patients with psychiatric disorders that investigates causes in order to develop clinical applications of the results, and to create applications to health services plans for individuals and/or communities. Written by a leading authority on social psychiatry and psychiatric epidemiology who has been residing in Nagasaki for most of his life, and also worked as a head of the WHO Collaborating Centre for Research and Training in Mental Health, it describes not only outstanding epidemiological studies and mental support reports for atomic bomb sufferers but also international collaborative projects on schizophrenia, affective disorders, and common mental disorders. This book provides a valuable resource not only for physicians and researchers in the field of psychiatry and mental health but for all those who work in the field of mental health.
Introduction -- I. Social Psychiatry and Psychiatric Epidemiology -- 1. Definition and Historical Review of Social Psychiatry and Psychiatric Epidemiology -- 1-1. Social Psychiatry and the Japanese Society of Social Psychiatry (JSSP) -- 1-2. Psychiatric Epidemiology -- 2. The Foundation of Psychiatric Epidemiology Research -- 2-1. Methodological Foundation -- 2-2. Ethics in Study Methods -- 2-3. Subjects of Epidemiological Studies in Psychiatry -- II. Findings on Social Psychiatry and Psychiatric Epidemiology in Japan -- 3. Activities of the Department of Neuropsychiatry, Nagasaki University School of Medicine, as a World Health Organization (WHO) Collaborating Center -- 4. Studies on Schizophrenia -- 4-1. Incidence Rates, Prevalence Rates, and Other Statistics -- 4-2. Findings of the WHO Collaborating Center in Nagasaki -- 4-3. Outline of Scales Used in the First Assessment for WHO/DOSMeD -- 4-4. Help-Seeking Patterns and Recognition by Family Members (Key Persons) in New Schizophrenia Cases in DOSMeD/Nagasaki -- 4-5. Subtypes of Schizophrenia -- 4-6. Psychiatric Symptoms of New Schizophrenia Cases in DOSMed/Nagasaki -- 4-7. Life Events and the Development of New Schizophrenia Cases in DOSMed/Nagasaki -- 4-8. Natural History and Outcome (in the Short and Long Term), and Associated Factors of New Schizophrenia Cases in DOSMed/Nagasaki -- 5. Studies on Affective Disorders -- 5-1. WHO World Mental Health Survey in Japan (WHO/WMH-J) -- 5-2. Summary of the Study on the Standardized Assessment of Depressive Disorder (SADD) -- 6. Studies on Patients with Affective Disorders in General Practice -- 6-1. Studies on Referral Rates in Patients with Depression in the General Health Care Setting -- 6-2. Studies on Medical Care in Patients with Psychological Problems in the General Health Care Setting -- 7. Development from Atomic Bomb Diseases to Survivors$1 (BMental Health Support: Findings on Disaster Psychiatry -- Appendix Medical Office (Ikyoku) -- Epilogue Further Developments in Social Psychiatry and Psychiatric Epidemiology.s
Keywords: Medicine; Neurosciences; Psychiatry; Epidemiology; Medicine & Public Health; Psychiatry; Epidemiology; Neurosciences; Medicine/Public Health, general